Corrigendum to ““Facebocrastination”? Predictors of using Facebook for procrastination and its effects on students' well-being” (Computers in Human Behavior (2016) 64 (65–76) (S0747563216304411) (10.1016/j.chb.2016.06.011)) - Meier, Adrian; Reinecke, Leonard; Meltzer, Christine E. (Computers in Human Behavior, 2017)
The authors regret a copy and paste error in the method section of Study 1 (p. 69). One of the four items of our measure of procrastination with Facebook is not reported correctly. Instead of the correct item (“I used Facebook while procrastinating upcoming work.”) the item “I used Facebook although I had more important things to do.” is listed twice in the respective paragraph (last paragraph in the left text column on p. 69). The authors would like to apologize for any inconvenience caused.
CRIS-Team Scopus Importer:2021-02-02